Edukasi Perawatan Kaki Diabetes kepada Kader Kesehatan: Diabetes Foot Care Education for Health Cadres - Sasmita, Hanum; Nurmalisa, Baiq Emy; Pangaribuan, Helena (Jurnal Pengabdian Masyarakat Lentora, 2023)
Introduction Central Sulawesi is ranked 10th with 2.2% of sufferers. If optimal prevention is not carried out from the start, the wound will deteriorate rapidly, and the worst is amputation. One of the efforts that can be made to prevent DFU from occurring is to do foot care. Foot care in people with DM is an attempt to avoid disturbances in the feet which, if continued, can lead to amputation. The goal to be achieved from this community service activity is to increase the knowledge of cadres in conducting education about Foot Care for Patients with Diabetes Mellitus in the Working Area of the Talise Health Center. The method used in this activity is a combination of lecture, discussion, demonstration and practice methods. The media used to help convey material is a leaflet. The activity begins with the preparation, implementation and evaluation stages. To find out the effectiveness of this activity, an apperception was carried out to measure the level of knowledge of the participants and at the end of the activity an evaluation was carried out by asking questions related to the material that had been presented and participants were asked to demonstrate DM foot care. Results The level of success in implementing this community service can be seen from the achievement of the number of participants, objectives and material targets. The number of participants who attended were 20 participants. Conclusion The purpose of the dedication was achieved, seen from the enthusiasm of the participants and at the end of the activity the participants were able to answer questions posed by the service team and were able to answer questions related to DM foot care. Suggestion It is hoped that the Talise Health Center will carry out similar activities on a regular basis and a larger number of participants so that all DM patients in the Talise Health Center work area have good knowledge and skills in performing foot care.